Thermochemical CO2 reduction over NiFe2O4@alumina filled reactor heated by high-flux solar simulator. (15th April 2020) - Guene Lougou, Bachirou; Shuai, Yong; Zhang, Hao; Ahouannou, Clément; Zhao, Jiupeng; Kounouhewa, Basile Bruno; Tan, Heping
Abstract: This paper investigated CO2 utilization into energy density chemical using NiFe2 O4 @Alumina support porous-medium filled reactor heated by high-flux solar simulator. A combination of numerical and experimental studies is developed to investigate the synthesis and characterization of the redox materials, thermal characteristics, redox reaction kinetics, and redox performance of NiFe2 O4 @Alumina support porous oxide material. Moreover, thermal and chemical energy conversion efficiency of NiFe2 O4 @Alumina support was analyzed. Considering the difficulty related to designing and manufacturing porous-medium filled solar thermal receiver, this study could provide tremendous innovation values and pattern impacts in the field of solar thermochemical (STC) energy conversion into fuels and chemicals. Highlights: NiFe2 O4 @Alumina exhibits higher thermal-chemical conversion performance. Thermal reduction of NiFe2 O4 @Alumina transits into hercynite class materials. Formation of Ni, Fe, NiO, FeO resulted in the weight loss of NiFe2 O4 @Alumina. Decrease in carbon deposit improves syngas yield. Increasing H2 yield results in high-density chemical energy flux.